Inequality, Poverty and the Intra-Household Allocation of Consumption in Senegal - De Vreyer, Philippe; Lambert, Sylvie (World Bank, Washington, DC, 2020)
Intra-household inequalities have long been a source of concern for policy design, but there is very little evidence. The current practice of ignoring inequality within households could lead to an underestimation of both overall inequality and poverty levels, as well as to the misclassification of some individuals as regards to their poverty status. Using a novel survey for Senegal in which consumption data were collected at a disaggregated level, this paper quantifies these various effects. In total, two opposing effects, one on mean and one on inequality, compensate each other in terms of the overall poverty rate, but individual poverty statuses are affected. Intra-household consumption inequalities accounts for 14 percent of inequality in Senegal. The authors uncover the fact that household structure and organization are key correlates of intra-household inequality and individual risk of poverty.